Peristaltic Effects on Flow of Hybrid Nanofluid in an Elliptic Duct With Elasticity - Devaki, P. (Communications in Mathematics and Applications, 2022)
This paper is focused on a hybrid nanofluid in an elliptic duct. The walls of the elliptical duct have two specific properties which include sinusoidal movement and elastic behavior. Elastic property is included in the model with the help of tension and radius relationships in two different ways. The cu/Ag/water hybrid nano model is considered in the present work. The equations governing the flow are resolved by the closed form technique. Comparison between two different combinations of nanoparticles is done graphically. The impact of elasticity, inlet pressure, outlet pressure, amplitude ratio, and other physical parameters on the flux of the nanofluid is observed. The elastic property of the wall is the innovative thought used in the present work and it finds its applications in the field of medicine.
Keywords: Elasticity; Inlet pressure; Outlet pressure; Elliptical duct; Hybrid nanofluid; Sinusoidal wave